Crossing borders international studies for the 21st century - Chernotsky, Harry I. (SAGE, 2013)
Today's international studies students need more than an overview of traditional academic disciplines - and more than oversimplified descriptions of global problems - to prepare for an increasingly globalized world. Chernotsky and Hobbs' new introductory text Crossing Borders offers a clear, compelling framework for understanding the global forces that both unite and separate world citizens. With smart features designed to promote critical thinking, the book invites students to envision the future roles they might play on the international stage and guides them in developing the intercultural competencies they need to get there.